INTERAKSI SOSIAL TRANSMIGRAN DESA WERDHI AGUNG DENGAN PENDUDUK ASLI DESA IBOLIAN DI KECAMATAN DUMOGA TENGAH - Claudia Mouren Demakota; Welson M. Wangke; Jenny ., Baroleh (Sam Ratulangi University, 2017)
This study aims to find out how cooperation, competition, conflict and accommodation between transmigration living in the village of Werdhi Agung with indigenous people in Dumoga Sub-district. This study was conducted from December 2016 to February 2017, starting from preparation to the formulation of the research report. The data used in the form of primary data and secondary data. This research is done by purposive sampling technique. The total respondents in this study were 40 people, who were the head of the family, consisting of 20 members of the transmigrant group from Bali and 20 members of the indigenous Mongondow community representing the local population. Data analysis was done descriptively by using Likert Scale. The results show that: a) The cooperation between transmigrants and indigenous peoples is so harmonious that in their daily life it has reflected a broad assimilation / mixing form arising from the realization that they have common interests, both individually and in groups, they are aware that they have different ethnic cultural backgrounds. This has a positive effect on the social life of transmigration communities and indigenous peoples in coexistence. b) Competition between transmigrants and indigenous people is marked by land ownership / social jealousy competition and competition between village youth but no competition or threat of violence. c) Conflicts between transmigrants and indigenous peoples only occur in land tenure, and the conflicts are not frequent among rural youth. d) Accommodation or work to end disputes or conflicts between conflicting parties ie between transmigrants and indigenous peoples can be resolved either through the family or with the help of villagers and government officials.